A 34-Year-Old Woman with Brainstem Cavernous Malformation: The Anterior Transcallosal Transchoroidal Approach and Literature Review - Hosainey, Sayied Abdol Mohieb; Meling, Torstein R. (Journal of Neurological Surgery Reports, 2014)
Mesencephalic cavernous malformations (MeCMs) account for 4 to 35% of the cavernous malformations of the central nervous system and are generally rare. Surgical resection of brainstem cavernomas are high-risk procedures and can be challenging to the neurosurgeon. Several approaches have been described, but the approach must allow for a straight line of sight in which the surgeon, the pial incision, and the MeCM are all collinear. This alignment provides the best view of the lesion while minimizing the need for brainstem retraction. The pial incision should be chosen to minimize the distance to the lesion while avoiding critical nuclei and tracts. In this case report, we present a 34-year-old woman with a MeCM resected by an anterior transcallosal transchoroidal approach with minimal damage to surrounding brain tissue. Although rarely used, it should be considered a valuable alternative to ventrally located brainstem cavernomas.
Keywords: cavernous malformation; brainstem cavernoma; surgical approach; transcallosal transchoroidal approach; surgical complications; brainstem hemorrhage